Menilik Manfaat Ekonomi dan Dampak Sosial Infrastruktur: Studi pada Proyek Bendungan Bagong di Kabupaten Trenggalek - Fadli, Alif Muhammad; Daulay, Anggi Anugerah; Muhammad, Balya Mahbuby; Mulya, Sintia Ahla; Juwita, Syerlin; Sakira, Tasya Fitri (Jurnal Pajak dan Keuangan Negara (PKN), 2025)
This research aims to identify the costs, economic benefits and social impacts of constructing Bagong Dam and determine the economic and social feasibility of building the dam. This research applies a mixed approach (quantitative-qualitative). The data collection method is carried out through literature review technique. This research shows that the construction of the Bagong Dam is economically feasible and will have an economic impact in the form of additional output, employment and increased workers' wages. The Bagong Dam also has social impacts, namely increasing community welfare, growth of the tourism sector in Trenggalek Regency, and reducing flood intensity. This research is expected to provide recommendations to the government in determining the economic and social feasibility of building Bagong Dam.